Implementasi Kebijakan Pendirian BUMDes Bunga Sari di Desa Tapung Jaya - Natasha, Elisabeth Michelle Levine; Marta, Auradian (Universitas Medan Area, 2025)
This study aims to analyze the effectiveness of policy implementation in establishing the Village-Owned Enterprise (BUMDes) Bunga Sari in Tapung Jaya Village, focusing on key influencing factors. Employing a descriptive qualitative approach and guided by Van Meter and Van Horn’s implementation theory, the analysis covers six core variables: policy standards and objectives, resources, implementing characteristics, dispositions, inter-organizational communication, and socio-economic-political conditions. Data were collected through in-depth interviews, field observations, and policy document analysis. The findings reveal that most BUMDes business units—particularly the savings and loan unit—operate effectively, significantly improving community access to capital and contributing to Village Original Revenue (PADes). Success is driven by positive implementer disposition, intensive communication, and strong local socio-political support. The study concludes that effective BUMDes implementation depends not only on regulation but also on adaptive and participatory governance. Theoretical contributions include expanding the application of implementation models in rural governance contexts, while practical contributions offer replicable best practices for strengthening community-based local economic development